Odpowiedzi

2010-01-19T20:05:51+01:00
X2-x dla x=7
7×2-7=7
a2-3a dla a=-4
-4×2-3×(-4)=4
1+x(x+4) dla x=-11
1+(-11)×(-11+4)=70
x-2y dla x-1 i y=-1
-1-2×(-1)=1
2x2-y(x+1) dla x=-2 i y=5
2×(-2)×2-5(-2+1)=13
(m + 1)(n-2) dla m=2 i n=1
(2+1)(1-2)=2-4+1-2=-3
3 1 3
Najlepsza Odpowiedź!
2010-01-19T20:07:17+01:00
1.7*7-7=49-7=42
2.-4*-4-3*-4=16+12=28
3.1-11*(-11+4)=-33*-7=231
4.1-2*-1=1+2=3
5.2*4-5*(-2+1)=8-5*-1=8+5=13
6.(2+1)*(1-2)=3*-1=-3
4 4 4
2010-01-19T20:07:44+01:00
X2-x dla x=7
7*2-7
=14-7
=7
a2-3a dla a=-4
-4*2-3*(-4)
=-8+12
=4
1+x(x+4) dla x=-11
1+(-11)*(-11+4)
=1-11*-7
=1+77
=78
x-2y dla x-1 i y=-1
-1-2*(-1)
=-1+2
=1
2x2-y(x+1) dla x=-2 i y=5
2*(-2)*2-5*(-2+1)
=-4*2-5*(-1)
=-8+5
=-3
(m + 1)(n-2) dla m=2 i n=1
(2+1)*(1-2)
=3*(-1)
=-3
1 5 1